2018
DOI: 10.1109/tpwrd.2017.2764386
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Bus-Transfer Switching in Future HVdc Substations

Abstract: Abstract-Prior research has characterized bus-transfer switching capabilities of disconnectors commonly found in ac gas insulated switchgear (GIS) by means of a limit performance prediction. A large number of dc bus-transfer tests was conducted on a modified bus-transfer test setup in order to study the applicability of these findings for the use of disconnectors in future HVdc substations. It was found that the ac extinction criterion based solely on the instantaneous recovery voltage and the expected arc vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 18 publications
1
24
0
Order By: Relevance
“…In prior research on the fundamentals of bus-transfer switching in HVac [14] and HVdc GIS [13] employing widely used GIS disconnectors with slow-moving and unblown electrode systems, the authors have identified a correlation between the instantaneous recovery voltage u RV and the predicted arc voltage u arc at a current zero at time t 0 , which ensures an extinction of the switching arc:…”
Section: Scope Of Researchmentioning
confidence: 99%
See 4 more Smart Citations
“…In prior research on the fundamentals of bus-transfer switching in HVac [14] and HVdc GIS [13] employing widely used GIS disconnectors with slow-moving and unblown electrode systems, the authors have identified a correlation between the instantaneous recovery voltage u RV and the predicted arc voltage u arc at a current zero at time t 0 , which ensures an extinction of the switching arc:…”
Section: Scope Of Researchmentioning
confidence: 99%
“…voltage level (L ) and pre-switching current (i S ·d 1 /(d 1 +d 2 )), these times become longer [13]. Another potential application of HVdc disconnectors, which can be modelled by the equivalent circuit diagram of Fig.…”
Section: Scope Of Researchmentioning
confidence: 99%
See 3 more Smart Citations